Conversão fermentativa de microalga Chlorella sp. em goma gelana por Sphingomonas paucimobilis - Saldanha, Loisleini Fontoura (2020)
Microalgae (MA) are potential feedstock for the production of fermentable monosaccharide, due to the appreciable carbohydrate fraction. The species used in this dissertation was Chlorella sp., one of the most resistant kind of MA. Thus, this research work aimed to convert MA biomass in gellan gum (GG) by fermentation with Sphingomonas paucimobilis. The physical-chemical treatment applied was pressurized acid hydrolysis, to weakening the biomass structure and making available fermentable sugars from the cellulosic fractions. The best results for microalgae (MA) in natura were 12.3 g of sugar L-1 for the pressurized sulfuric hydrolysis (150 °C, 2.5% v v-1, 36.6 min) and 12.5 g of sugars L-1 for the pressurized hydrochloric hydrolysis (155 °C, 1.5% v v-1, 40 min). Activated carbon (50 ºC, 10% m v-1, 60 min) was used to detoxify MA hydrolyzate, making possible the use of this hydrolyzate as fermentative medium for Sphingomonas paucimobilis. Using multivariate approach to optimize the culture conditions, temperature (20-30 ºC) and orbital agitation (120-240 rpm) of the fermentation stage were evaluated. Under optimized conditions (pH 7.0, 7.0 g yeast extract L-1, 30 ºC, 240 rpm) the production of GG, extracted with cooled ethyl alcohol, resulted in 53.3 g L-1 of hydrolyzate, after 60 h of cultivation. The analytical method make use of a High Performance Liquid Chromatograph coupled to Refractive Index Detector (HPLC-RID), applying figure-of-merit and method validation studies. The characterization of GG was done by Fourier Transform Infrared Spectrometry (FT-IR) and Gel Permeation Chromatography (GPC). The viability of using MA for sugar production was demonstrated on lab scale, and, the viability of bioconversion into GG (91.7% purity), throughout an innovative production route. Adittionally, a preliminary economic evaluation of the process was provided.